TINJAUAN YURIDIS TERHADAP PENERAPAN ASAS UNUS TESTIS NULLUS TESTIS DALAM TINDAK PIDANA PENCABULAN ANAK DI BAWAH UMUR DI TINJAU PASAL 185 AYAT (2) KITAB UNDANG – UNDANG HUKUM ACARA PIDANA. - Adipura, Kelvin (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
AbstractThe problem in this study is how the application of the principle of the testus principle of the testus in the criminal acts of underage children and also how the strength of the witnesses of children under age in the criminal acts of sexual abuse of minors.Proof in criminal cases according to Article 184 of the Criminal Procedure Code requires the existence of legal evidence. The judge can impose a criminal offense under Article 183 of the Criminal Procedure Code, at least two valid evidences that can shape the judge's conviction about the defendant's fault. The establishment of the judge's conviction in imposing criminal decisions is based on the results of examination of the evidence presented in the trial.Provisions regarding the use of one witness not a witness not a witness to the Testus Nullus Testis in the Criminal Procedure Code are regulated in Article 185 paragraph (2). Based on the provisions of the article, just to prove the fault of the accused a witness is not enough. However, the testimony of one witness can be recognized if accompanied by valid evidence as stipulated in Article 185 paragraph (3) of the Criminal Procedure Code. And if you look at the provisions of Article 183 of the Criminal Procedure Code, the Judge may not impose a sentence on a person except if with at least two valid pieces of evidence he has the conviction that a criminal act actually occurred and that the accused is guilty of doing so.Article 184 paragraph (1) of the Criminal Procedure Code, valid evidence includes witness statements, expert statements, letters, instructions, statements of the defendant. Proof of evidence is in the form of the results of Visum et Repertum (VER) made by officials and made on the oath of office based on the provisions of legislation as stipulated in Article 187 of the Criminal Procedure Code letter c.